Distinct subcellular localization of tau and alpha-synuclein in lewy body disease - D. Luke Fischer; Marissa Menard; Omar Z. Abdelaziz; Nicholas M. Kanaan; Virginia G. Cobbs; Richard E. Kennedy; Geidy E. Serrano; Thomas G. Beach; Laura A. Volpicelli-Daley (Acta Neuropathologica Communications)
Abstract Lewy bodies and neurofibrillary tangles, composed of α-synuclein (α-syn) and tau, respectively, often are found together in the same brain and correlate with worsening cognition. Human postmortem studies show colocalization of α-syn and tau occurs in Lewy bodies, but with limited effort to quantify colocalization. In this study, postmortem middle temporal gyrus tissue from decedents (n = 9) without temporal lobe disease (control) or with Lewy body disease (LBD) was immunofluorescently labeled with antibodies to phosphorylated α-syn (p-α-syn), tau phosphorylated at Ser202/Thr205 (p-tau), or exposure of tau’s phosphatase-activating domain (PAD-tau) as a marker of early tau aggregates. Immunofluorescence for major-histocompatibility complex class 2 (MHCII) and ionized calcium binding adaptor molecule 1 (Iba1) also was performed because inflammation is an additional pathological hallmark of LBDs, and they were a positive control for two markers known to colocalize. The abundance of p-α-syn, p-tau, and MHCII was significantly associated with diagnosis of LBD. Quantification of colocalization showed that MHCII and Iba1 colocalized, demonstrating activated immune cells are mostly microglia. However, p-α-syn rarely colocalized with p-tau or PAD-tau, although the overlap of p-α-syn with PAD-tau was significantly associated with LBD. In the rare cases pathologic α-syn and pathologic tau were found in the same Lewy body or Lewy neurite, tau appeared to surround α-syn but did not colocalize within the same structure. The relationship between tau and α-syn copathology is important for explaining clinical symptoms, severity, and progression, but there is no evidence for frequent, direct protein-protein interactions in the middle temporal gyrus.